The isotopic evolution of atmospheric Pb in central Ontario since AD 1800, and its impacts on the soils, waters, and sediments of a forested watershed, Kawagama Lake - Shotyk, William; Krachler, Michael (Geochimica et cosmochimica acta, 2010)
A peat core from an ombrotrophic bog documents the isotopic evolution of atmospheric Pb in central Ontario since AD 1804±53 (210Pb dating). Despite the introduction of unleaded gasoline in the mid-1970’s, the ratio 206Pb/207Pb in atmospheric deposition has not increased as expected, but rather continues to decline. In fact, snowpack sampling (2005 and 2009) and rainwater samples (2008) show that the isotopic composition of atmospheric Pb today is often far less radiogenic than the gasoline lead that had been used in Canada in the past. The peat, snow, and rainwater data presented here are consistent with the Pb isotope data for aerosols collected in Dorset in 1984 and 1986 which were traced by Sturges and Barrie (1989) to emissions from the Noranda smelter in northern Quèbec, Canada’s largest single source of atmospheric Pb. Understanding atmospheric Pb deposition in central Ontario, therefore, requires not only consideration of natural sources and past contributions from leaded gasoline, but also emissions from metal smelting and refining. Lead in the streams which enter Kawagama Lake today (206Pb/207Pb=1.16−1.19) represents a mixture between the natural values (1.191−1.201 estimated using pre-industrial lake sediments) and the values found in the humus layer of the surrounding forest soils (206Pb/207Pb=1.15−1.19). In the lake itself, however, Pb is much less radiogenic (206Pb/207Pb as low as 1.09) than in the streams, with the dissolved fraction less radiogenic than particulate material. The evolution of Pb isotope ratios within the watershed apparently reflects preferential removal by sedimentation of comparatively dense, radiogenic, terrestrial particles (derived from the mineral fraction of soils) from the humus particles with lower ratios of 206Pb/207Pb (because of atmospheric Pb contamination). Despite the contemporary enrichments of Pb in rain and snow, concentrations of dissolved Pb in the lake are extremely low (sometimes below 10ng/l), with Pb concentrations and Pb/Sc ratios approaching “natural” values because of efficient binding to particles, and their subsequent removal in the watershed.
Gesehen am 19.07.2023